Produção de IL-6 e IL-1β em cultivos ex vivo de endométrio bovino inoculados com Leptospira interrogans sorovar Hardjoprajitno - Gomes, Dayane Olímpia (2020)
Leptospirosis is a zoonosis caused by a bacteria belonging to genus Leptospira spp. There are reports of this bacteria isolation in the female reproductive tract with are related to abortion and subfertility in bovine herds. It is known that Leptospira presence in reproductive organs of bovines promotes tissue damages especially by vasculitis. Moreover, acute leptospirosis produces high levels of cytokines during the onset of infection. However, few studies were performed about the pathogenesis of this microorganism in the endometrium of cows. The objective of this study was to evaluate the inflammatory cytokines profile after Leptospira interrogans serovars Hardjoprajitno and LPS of Escherichia coli challenges produced by uterine tissue ex vivo of non-pregnant and pregnant cows serologically reactive or not to Microscopic Agglutination Test (MAT). A total of 43 uterus with respective blood samples were collected from crossbred cows, from those 19 were non-pregnant and 24 pregnant, without any clinical disease evidence. To determine the pregnancy phase, the measurement of fetuses were performed. To analyze previous infection occurrence antibodies against Leptospira were evaluated by MAT. After endometrium exposure, fragments of endometrium tissue (explants) were collected using a punch of 8 mm in intercaruncular region. The processing of endometrial explants were done in a 24-well cell culture plates. The solutions added on explants were: a) Control medium (2 mL of RPMI solution); b) RPMI medium (1μg/mL of LPS from Escherichia coli); c) EMJH medium with inoculum of Leptospira interrogans serovars Hardjoprajitno (108 leptospires/mL). The plates were incubated at 37°C with 5% of CO2 for 24 hours. After this period, uterine explants were weighed and collected and subsequently tested for interleukins (IL-1β and IL-6) production profile by ELISA kits. Considering the challenge with 1μg/mL of LPS, both pregnant and non-pregnant cows build a response due to challenge with a significant increase in IL-1β and IL-6 production compared to control group. Considering the challenge with Leptospira, an increase of IL-6 concentration was verified in the explants of both pregnant and non-pregnant cows related to control. However, only the explants from non-pregnant cows showed an increase of IL-6 production related to control. In the individual evaluation of pregnancy phases, during the initial phase (first trimester) only occurred significant IL-6 production, differing from IL-1β which significant production increase occurred during late gestation phase in the challenge with 1μg/mL of LPS from E.coli. There was no difference in cytokines production according to pregnancy phase after challenge with Leptospira. In conclusion, a higher stimulation of cytokines production was verified in endometrial tissues of reagent cows after LPS and Leptospira challenges; lower stimulation of IL-6 production in pregnant cows after Leptospira challenge; a higher stimulation during initial and late pregnancy phases after LPS from E.coli challenge, and no significant difference between pregnancy phases after Leptospira challenge.